2016
DOI: 10.1007/s00268-016-3681-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Simulated Model to Teach Male Adult Circumcision in Sub‐Saharan Africa

Abstract: Male adult circumcision (MC) has been shown to reduce the risk of HIV transmission in men by 50-60 %. An upscaling in the training of providers to perform circumcision is necessary to meet demand since MC is a key component of essential surgery in the context of universal health coverage. We piloted a low-cost, high-fidelity model for training adult circumcision. Multi-centre, multinational data were collected on 74 trainees and clinicians (trainers) in sub-Saharan Africa. Both trainers and trainees gave excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Whilst the virtues of simulation training have become established in HICs [14,15] our literature review of simulation training in surgical specialities in SSA found only 19 papers of which four were urological [13,[32][33][34]; none were RCTs.…”
Section: Simulation Training In Urology and Its Adoption In Ssamentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the virtues of simulation training have become established in HICs [14,15] our literature review of simulation training in surgical specialities in SSA found only 19 papers of which four were urological [13,[32][33][34]; none were RCTs.…”
Section: Simulation Training In Urology and Its Adoption In Ssamentioning
confidence: 99%
“…Other examples of low-cost low-fidelity models include a wooden penile model (initial cost of £7 and a recurrent cost of £4) for circumcision training used in Uganda [34], although their study lacked trainees' feedback. Campain et al [33] described a low-cost but high-fidelity circumcision simulation model with 'very good' or 'excellent' for appearance and realism of suturing in 60% and 71%, respectively, of trainees from seven African countries.…”
Section: Models For Simulation Training In Lmicsmentioning
confidence: 99%
“…To establish content validity, feedback from trainers was analysed (appearance and realism were rated as ‘very good’ or ‘excellent’ in 94 and 63%, respectively). Face validity was assessed by seeking feedback from trainees, who rated the model as either ‘very good’ or ‘excellent’ for appearance and realism of suturing in 60 and 71%, respectively [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific simulation models have been validated in high-income countries [ 47 ] but there are few examples of either new or existing models being validated for use in the different and diverse educational setting of SSA. Studies which have attempted to assess validity in SSA have only sought self-reported feedback from participants [ 13 , 14 ] and so no conclusions on transferability to real world operative practice can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…This study is potentially important because there are few prior studies about teaching through low-cost simulation models in low-income countries. [14][15][16] The guidelines of the World Health Organization (WHO) for health professional education recommend high fidelity methods for training in settings with appropriate resources with a moderate level of evidence towards this recommendation. 17 Rwanda has seen considerable growth in the more than 20 years since the genocide and this time period includes major advances in the health sector.…”
Section: Discussionmentioning
confidence: 99%